Description of Fecal Culture Results in Diarrhea Patients Due To Antibiotic Use - Suci Tresna; I.G.A.A Putri Sri Rejeki; Puspa Wardhani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Diarrhea infection is common in developing countries and causes death of around 3 million people every year. Diarrhea is also the second leading cause of death in infants. Riskesdas in 2013 showed 30,775 cases of diarrhea. Causes were such as bacterial infections Salmonella, Shigella, Vibrio, Entamoeba, and Yersinia. Other influences can occur due to viral and fungal infections. Diarrhea is a nosocomial infection that is common in hospitalized patients due to the long-term use of antibiotics caused by Clostridium difficile. This study was a follow-up study of diarrhea patients who received antibiotic therapy for more than two days with the results of C.difficile negative toxin, then continued with fecal culture examination. This study aimed to look at the description causes of diarrhea other than C.difficile in patients who received long-term antibiotic therapy. This research is an observational study. Samples were taken from 30 diarrhea patients with 2 x 24 hours of antibiotic use who were hospitalized in the ICU, Dr. Soetomo Hospital Surabaya from August 2017 to May 2018. Samples with negative C.difficiletoxin results were then followed by fecal culture examination using conventional methods. The results of culture examination from 30 samples showed three samples with positive culture results extended-spectrum Î² lactamase producing E.coli, two samples positive culture just E.coli, and 25 other samples showed negative culture results. The results of the fecal culture examination showed a description of causes of diarrhea in patients who received antibiotic therapy was pathogenic E.coli (ESBL). The possibility of other causes that cannot be detected from the culture such as viral and fungal infections, still requires further research.